دور المؤشرات المالية في تقويم الأداء المالي في المصارف الإسلامية العاملة في سورية - العمار رضوان; مهنا زينب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تهدف الدراسة إلى تقويم الأداء المالي للمصارف الإسلامية العاملة في سورية باستخدام المؤشرات المالية خلال الفترة 2009) _ 2015)، وإلى دراسة العوامل المؤثرة في الأداء المالي للمصارف المدروسة. حيث تمت دراسة العلاقة بين تقويم الأداء المالي كمتغير تابع مقاساً: بمعدل العائد على الأصول، معدل العائد على حقوق الملكية، معدل العائد على الودائع، وربحية السهم، وبين المتغيرات المستقلة الآتية: القدرة على جذب المدخرات، توظيف الأموال، السيولة والمخاطر، الربحية، والأزمة في سورية. تمّ استخدام أساليب تحليل بيانات السلاسل الزمنية المقطعية (Panel Data) من خلال تقدير نموذج الانحدار المجمع (Pooled Model) ونموذج الآثار الثابتة (Fixed Effects). خلصت الدراسة إلى وجود علاقة إيجابية ذات دلالة إحصائية بين توظيف الأموال وتقويم الأداء المالي للمصارف المدروسة، وإلى وجود علاقة سلبية ذات دلالة إحصائية بين الربحية وتقويم الأداء المالي للمصارف المدروسة. كما توصلت الدراسة إلى عدم وجود علاقة ذات دلالة إحصائية بين كل من القدرة على جذب المدخرات، السيولة والمخاطر، الأزمة في سورية وبين تقويم الأداء المالي للمصارف المدروسة. The study aims to evaluate the financial performance of Islamic banks in Syria by using financial ratios during the periods (2009_2015), and study the factors affecting on financial performance of those banks. This was based on studying the relationship between financial performance evaluation as dependent variable measured by (return on assets, return on equity, return on deposits, and earnings per share) and the following independent variables (deposits, investment, liquidity and risk, profitability, and crisis in Syria). The study employed the methods of Panel Data through estimating Pooled Regression and Fixed Effects Models. The study concluded that there is a significant positive relation between the investment and the bank financial performance evaluation. There is a significant negative relation between the profitability and the bank financial performance evaluation. And there is no significant relation between (the deposits, the liquidity and risk, the crises) and the financial performance evaluation in Islamic banks in Syria.